CD206+ Cell Number Differentiates Influenza A (H1N1)pdm09 from Seasonal Influenza A Virus in Fatal Cases - Rodríguez Ramírez, Heidi Giselle; Salinas Carmona, Mario César; Barboza Quintana, Oralia; Melo de la Garza, Américo; Ceceñas Falcón, Luis Ángel; Rangel Martinez, Lilia M.; Rosas Taraco, Adrián Geovanni (2014)
In 2009, a new influenza A (H1N1) virus affected many persons around the world. There is an urgent need for finding biomarkers to distinguish between influenza A (H1N1)pdm09 and seasonal influenza virus. We investigated these possible biomarkers in the lung of fatal cases of confirmed influenza A (H1N1)pdm09. Cytokines (inflammatory and anti-inflammatory) and cellular markers (macrophages and lymphocytes subpopulation markers) were analyzed in lung tissue from both influenza A (H1N1)pdm09 and seasonal influenza virus. High levels of IL-17, IFN-